Emotional Intelligence and Online English Language Learners’ Academic Achievement - Saira Maqbool (PJDOL, 2019)
This paper investigates the correlation between academic achievement of ESL learners and their emotional intelligence. Data from 122 distance education graduate students both male and female, was collected using Bar-one emotional quotient inventory EQ adopted from Mixed Model of EI by Mayers (2007). The sample was selected through convenient sampling technique. The correlation of inventory was correlated with the GPA’s of the students to find relationship between emotional intelligence and online English language learners’ academic achievement and to know the level of relationship between each emotional intelligence subscale and English language learners’ academic achievement. The data obtained was treated in SPSS 22 version. Pearson correlation was applied to draw the results. The result revealed that there exists significant relationship between emotional intelligence and the level of ESL learners’ achievement at graduate level. According to the findings of this research some applicable recommendations are suggested.